Developing digital interactive on heat transfer concept for elementary students - Hermita, Neni (2021)
The learning trend in the 21st century is based on digital learning. This study aims to develop learning media in the form of a digital interactive on heat transfer concept for elementary students which is expected to overcome learning during the Covid-19 pandemic. The method of study used the ADDIE Model. The involves media experts and material experts as validators of the media being developed. The data collected in the form of a validity questionnaire and open questions. Data analysis by calculating the average percentage score which can be seen from the aspect of appearance, material aspects, and teacher responses and student responses. The results obtained from the media validity test show that the digital interactive on heat transfer concept is in the valid category with a percentage score of 79, 71%. The development of the digital interactive on heat transfer concept is said to be valid because it has met the assessment criteria seen from the appearance, material, and language. While the results obtained from the limited trial showed positive comments from students and the evaluation stage through student and teacher responses showed that the interactive media of conductor and insulator material was very practical with a percentage score of 91.37%. This shows that the digital interactive on heat transfer concept is suitable for use by teachers and students in learning. This research is expected to assist educators in using science learning media in elementary schools, especially the concept of heat transfer, and can be a reference for other researchers in developing interactive digital media in elementary schools.